OSTEOARTHRITIS (Homoeopathy for All, 2022)
Osteoarthritis (OA) is a disease  marked by progressive joint failure  in which all structures of the joint  have undergone pathologic change.  The pathologic changes of OA  are hyaline articular cartilage loss  accompanied by increasing thickness  and sclerosis of the subchondral  bony plate, outgrowth of osteophytes  at the joint margin, stretching of the  articular capsule, and weakness of  the muscles bridging the joint. There  are numerous pathways that lead to  OA, but the initial step is often joint  injury in the setting of a failure of  protective mechanisms. Osteoarthritis most commonly  affects the hands, lower back, neck,  and weight-bearing joints such as  knees, hips, and feet.
Keywords: Osteoarthritis; bony plate; weight-bearing